Effects of Rubber Chain Exercises and Dietary Control on Overweight Female Adults - Leartwanawattana, Janpen; Sukkum, Worarat; Sumrit , Waranee; Sanee, Nuntaya (JOURNAL OF SOUTHERN TECHNOLOGY, 2021)
Overweight adults are at increased risk for many chronic diseases, compared to adults who meet weight standards. Although the Ministry of Public Health established campaigns for obesity prevention, obesity rates for adults have increased gradually, particularly female adults. Thus, this quasi-experimental study aimed to investigate the effects of self-regulatory skill usage with rubber chain exercise and dietary control on weight management in overweight female adults. Fifty female adults aged 35-59 years old with overweight were recruited to participate in the study using a multistage sampling procedure. Each twenty-five participants were assigned to experimental and control groups. The experimental group received the self-regulatory skill usage program consisting of the nutrition flag for the dietary control handbook, the rubber chain exercise handbook, the self-regulation record of rubber chain exercise, and the self-regulation record of dietary control. Both groups were measured using the demographic, the rubber chain exercise behavior, the dietary control behavior questionnaires. Moreover, participants’ body weights were measured at pre-post intervention. Data were analyzed using frequency, mean, standard deviation, and ANCOVA. The findings revealed that the mean scores of the experimental group were significantly higher in rubber chain exercise behavior (1.57± 0.51), dietary control behavior (1.99± 0.30), and body weight (mean=62.46 ± SD=7.85, p = .05) at the end of the intervention than the control group (0.00±0.00) (1.36±0.28 and 66.20±7.48). Per the findings of the study, the self-regulatory skill usage with rubber chain exercise and dietary control program should be implemented in female adults with overweight in order to prevent them from obesity-related chronic diseases.